Hubungan Pengetahuan Dan Dukungan Keluarga Terhadap Perilaku Lansia Dalam Pengendalian Hipertensi Di Kelurahan Cipete Utara Kecamatan Kebayoran Baru Jakarta Selatan Tahun 2023 - Herawati, Shilvia Mutiara (JURNAL PENDIDIKAN KESEHATAN, 2024)
Hypertension is a common public health problem in developing countries. Hypertension is one of the non-communicable diseases (NCD) and causes very serious health problems. Factors that occur in the incidence of hypertension due to behavioral risk factors, namely lack of fruit and vegetable consumption, excessive alcohol consumption, lack of physical activity and poor stress management. The purpose of this study was to determine the relationship between knowledge and family support for the behavior of the elderly in controlling hypertension in North Cipete Village, Kebayoran Baru District, South Jakarta in 2023. This study is a quantitative research study with a Cross Sectional design. The population in this study were elderly hypertension in Cipete Utara Village in 2023 with a total population of 1.672 people, the number of samples consisted of 70 people who had entered the inclusion and exclusion criteria. The sampling technique in this study was cluster random sampling and the data analysis used was univariate and bivariate analysis using the Chi Square test. Univariate results show that elderly people's behavior in controlling hypertension is poor (60%), they have poor knowledge (81.4%), and they have less supportive family support (62.9%). Bivariate results show that there is a relationship between knowledge and behavior in controlling hypertension in the elderly (0.000) and there is a strong relationship between family support and behavior in the elderly in controlling hypertension (0.010). Elderly people are expected to improve their health, both knowledge and behavior, and be supported by a supportive family. Routine health checks at least once a month need to be done to control hypertension in the elderly. Keywords: Hypertension, Knowledge, Family, Control Behavior